Institutional Racism in Ellison's Invisible Man and Lee's To Kill a Mockingbird (Damascus University Journal of arts and humanities sciences, 2023)
This paper discusses the negative impact of institutions in the United States controlled by white racists on black individuals. These racist practices aim at maintaining white sovereignty over American society. White racists use the institutional context to subjugate blacks and deprive them of their basic human rights. In Ellison’s Invisible Man and Lee’s To Kill a Mockingbird, educational, medical and judicial institutions appear to be tools that  implement racist attitudes inherited from the time of slavery. Black characters encounter humiliating experiences in different American institutions due to their skin color and the stereotypes that are imposed on them.
Keywords: Institutional racism; black individuals; white racists; dominance; subjugation